Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1137/140959055
|View full text |Cite
|
Sign up to set email alerts
|

Measure Valued Directional Sparsity for Parabolic Optimal Control Problems

Abstract: A directional sparsity framework allowing for measure valued controls in the spatial direction is proposed for parabolic optimal control problems. It allows for controls which are localized in space, where the spatial support is independent of time. Well-posedness of the optimal control problems is established and the optimality system is derived. It is used to establish structural properties of the minimizer. An a priori error analysis for finite element discretization is obtained, and numerical results illus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
93
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 21 publications
3
93
0
Order By: Relevance
“…This agrees to some extent with previous contributions on optimal control with measures, cf. [3,4,15,18], where it is also observed that this error decays faster than linear. The error ȳ − y σ (ū) L 2 (Q) converges quadratically, which is in accordance with Proposition 4.2.…”
Section: Discrete Optimality Conditions and Regularization Sincementioning
confidence: 75%
See 2 more Smart Citations
“…This agrees to some extent with previous contributions on optimal control with measures, cf. [3,4,15,18], where it is also observed that this error decays faster than linear. The error ȳ − y σ (ū) L 2 (Q) converges quadratically, which is in accordance with Proposition 4.2.…”
Section: Discrete Optimality Conditions and Regularization Sincementioning
confidence: 75%
“…Since g : M(0, T ) −→ R is convex and continuous and D t : BV (0, T ) −→ M(0, T ) is a linear and continuous mapping, we can apply the chain rule [11, Chapter I, Proposition 5.7] to deduce that ∂(g • D t )(u) = D * t ∂g(u ), which immediately leads to (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A priori error estimates for finite element approximation of linear elliptic optimal control problems with measure valued controls were investigated in [16]. The parabolic case was considered in [6,13] with different measure valued topologies to enhance directional spatial sparsity. The terminology directional sparsity was introduces in [12].…”
Section: Introductionmentioning
confidence: 99%
“…Corresponding optimal control problems with linear elliptic and parabolic equations have been studied in [11], and the term directionally sparse controls was coined there. An extension of this work to measure-valued controls can be found in [13].…”
Section: Introductionmentioning
confidence: 99%